What to ask the person in the mirror : critical questions for becoming a more effective leader and reaching your potential - Kaplan, Robert Steven. (Harvard Business Review Press, 2011)
Great leadership is not about having all the answers- it is, more often, about having the courage to ask the critical questions. In What to Ask the Person in the Mirror, Robert Kaplan offers a concise and engaging guide to help executives improve their effectiveness as leaders. At the core of the book is a series of critical questions to help you lead your organization more successfully and take ownership of your career.--[book jacket]